Enhancing students' learning motivation through bibliocounseling technique - Sari, Eva Kartika wulan (COUNS-EDU: The International Journal of Counseling and Education, 2019)
The present study aimed at enhancing students' learning motivation using bibliocounseling technique. This was a pre-experimental study with one group pretest-posttest design. The subjects of the study were 11th grade students of a Senior High School. They were selected through purposive random sampling. The instrument of the study consisted of learning motivation scale and observation guide. The data of the study were analyzed by descriptive analysis and Wilcoxon test. The result of the study showed that there was a difference between the score of pre-test and post-test, there was a 37% increase from the category of intermediate into high. While, the result of statistical analysis on the Wilcoxon test exhibited the significance value of 0.011 < 0.05, in other words, there is differences between pre- and post- treatment, therefore, the proposed hypothesis was accepted. The result of the study showed that the subjects experienced learning motivation improvement because he/she implemented bibliocounseling. Therefore, it could be concluded that bibliocounseling technique is effective to improve students’ learning motivation.